Regional citrate anticoagulation for continuous renal replacement therapy in pediatric patients with liver failure. - Keila Rodriguez; Poyyapakkam R Srivaths; Leyat Tal; Mary N Watson; Alyssa A Riley; Ryan W Himes; Moreshwar S Desai; Michael C Braun; Ayse Akcan Arikan (PLoS ONE)
Pediatric liver failure patients frequently develop multiple organ failure and require continuous renal replacement therapy (CRRT) as part of supportive therapy in the pediatric intensive care unit. While many centers employ no anticoagulation for fear of bleeding complications, balanced coagulation disturbance predisposes these patients to clotting as well as bleeding, making maintenance of longer circuit life to deliver adequate dialysis clearance challenging. Regional citrate anticoagulation (RCA) is an attractive option as it avoids systemic anticoagulation, but since citrate metabolism is impaired in liver failure, concerns about toxicity has limited its use. Pediatric data on RCA with liver failure is very scarce. We aimed to establish safety and efficacy of RCA in pediatric liver failure patients on CRRT. Retrospective review of pediatric patients with liver failure receiving CRRT over 30 months. Demographic data and CRRT related data were collected by chart review. Citrate accumulation (CA) was defined as total calcium (mg/dl) /ionized calcium (mmol/L) ratio >2.5 for > 48 hours. Efficacy was assessed by filter life. Safety was assessed by frequency of adverse events ((AEs) defined as bleeding, hemodynamic instability, arrhythmias). Fifty-one patients (median age 3.5 (IQR 0.75-14.2) years) received 861 CRRT days; 70% experienced at least one episode of CA, only 37% were recorded as such in the medical record. AE rate was 93/1000 CRRT days and did not differ between CA days and others. Median filter life was 66 hours (IQR 29-74); 63% filters lasted longer than 48 hrs. Though common, CA was not associated with increased AEs on in pediatric liver failure patients on CRRT receiving RCA. Filter life was adequate. RCA appears an effective anticoagulation for CRRT in pediatric liver failure. Application of a structured definition would increase recognition of CA to allow timely intervention.